The role of talent management in creating a competitive advantage for vocational high school teachers in the era of globalization - Rudi Yanto Batara Silalahi; David Panjaitan (Junal Ilmu Manajemen, 2023)
This research aims to investigate the important role of talent management in addressing various challenges faced by vocational high school (SMK) teachers in the context of identifying and recruiting talented teachers, developing skills and knowledge, motivating and rewarding, and maintaining and retaining talented teachers. In an increasingly complex globalized era, SMK teachers must possess relevant qualifications and competencies to meet the demands of the time in order to create competitive advantages. However, managing talent in SMK teachers remains a concern. This research can contribute to providing greater insights and understanding about the importance of talent management in the context of SMK education. This research is based on a literature review, where various relevant literature sources are examined and described in a descriptive manner. The findings of this research reveal that talent management plays a central role in identifying and recruiting talented teachers through a comprehensive selection process. Additionally, talent management supports the development of skills and knowledge of SMK teachers through relevant training and professional development programs tailored to the needs of the industry. Furthermore, talent management is involved in motivating and rewarding SMK teachers through recognition and appropriate incentives. Lastly, talent management assists in the maintenance and retention of talented teachers through proper placement, clear career development, and ongoing professional support.